Constitutional Piety: The Integration of Anti-Corruption Education into Islamic Religious Learning Based on Neuroscience - Suyadi, Suyadi; Sumaryati, Sumaryati; Hastuti, Dwi; Yusmaliana, Desfa; Rahmah MZ, Rafika Dwi (J-PAI: Jurnal Pendidikan Agama Islam, 2019)
Abstract. The new phenomenon of corruption cases that ensnared Islamic religious leaders in Indonesia indicates that so far Islamic education in Indonesia has not taught anti-corruption. As a result, religious leaders only have ritual and social piety, but do not yet have constitutional piety. From a neuroscience perspective, Corruptor's brain is basically normal but not healthy. The purpose of this study is to find a conceptual model of the integration of anti-corruption education in neuroscience-based Islamic religious learning to develop character constitutional piety. The research approach used is qualitative method in the form of Creswell model library research. Data sources are obtained from literature in the field of Islamic education, anti-corruption, and neurosciences. The Sugiyono model was performed to collect the data, namely by searching related literature, both manually and digitally. The data were then analyzed using Moleongâ€™s content analysis. The results showed that the character of constitutional piety could be developed in students through anti-corruption education integrated with neuroscience-based Islamic religious learning. Seven forms of corruption (detrimental to the state, bribery, embezzlement, extortion, cheating, conflict of interest and gratification) are examined in perspective of jinayah jurisprudence and or anti-corruption jurisprudence (al- ghÃ»l, riswah, khiyanat, ghasbah) then formally configured. The anticorruption education model in Islamic religious learning based on neuroscience has the potential to develop the character of ritual, social and constitutional piety integrally.Keywords. Islamic Education; Anti-corruption; Neuroscience; Ritual Piety; Social and Constitutional.